Cognitive development across different age ranges in late adulthood - Argimon, Irani Lima; Pontificia Universidade Católica do Rio Grande do Sul (2013)
This study sought to assess the cognitive development of older adults in different age groups, examining subjective perception of memory, verbal fluency, orientation in time and space, memory, and attention. The sample consisted of 121 subjects randomly selected, between the ages of 60 and 95 years, of both sexes and with varied educational attainment, took part in the study. Data were collected with a sociodemographic questionnaire, the Geriatric Depression Scale (GDS), the subjective Memory Complaint Questionnaire (MAC-Q), the Mini-Mental State Examination (MMSE), the Digit Span subtest of the Wechsler Adult Intelligence Scale, Revised (WAIS-R), the Buschke Selective Reminding Test, and a category verbal fluency test (animals). Results showed an inverse correlation between subjective perception of memory complaints and cognitive test performance. Age and educational attainment influenced cognitive test performance. Younger subjects and those with a higher educational attainment scored better on the verbal fluency test, MMSE, and digit span.